Comparative analysis of the impact of industrial and agricultural effluents on Ona stream in Ibadan, Nigeria (Journal of Science and Technology, 2016)
The comparative assessment of industrial and agricultural effluents on surface water qualities of Ona Stream at Oluyole industrial Estate was carried out. This was to identify major pollutants, their effects on water qualities and to ascertain the potential of using the polluted surface waterfor irrigation purposes. Water samples were collected at pre-determined points along the stream and major parameters were analyzed using standard procedures. Physiochemical and microbiological tests carried out indicated that some parameters gave evidence of pollution due toindustrial effluent discharge. The range of values of some of these parameters included dissolved oxygen (DO) 3.0 – 5.5 mg O2/l, chemical oxygen demand (COD), 64-255 mg O2/l and biochemical oxygen demand (BOD), 26-70 mg/l. Others were total dissolved solids (TDS), 1285-2090mg/l and Oil and grease, 6.8-3.4 mg/l. As for agricultural effluents parameters, DO ranged between 1.62 and 5.10mg O2/l, BOD was 26-480 mg/l, COD, 64-1750 mg O2/l and TDS was between 1285 and 2250 mg/l. All the values are above the Federal Environmental Protection Agency (FEPA) maximum allowable limit for effluent discharge into surface water. The statistical analyses carried out showed significant differences in all the physiochemical and heavy metal parameters analyzed at 5% significance level. Usage of Ona stream for domestic and irrigation purposes was not encouraged due to the health hazards it poses as the presence of contaminants and heavy metal pollution in large quantities confirmed this. Development of clean water technology for water pollution control and application of appropriate polices to compel industries to treat effluent before discharging into the stream are some of the recommendations suggested.